Methodology of assessing the personality qualities of junior female gymnasts (12- 14 years old) - Potop, V. (Science, Movement & Health, 2013)
The purpose of the paper is to highlight the methodology of assessment of personality qualities of junior female gymnasts 12 to 14 years old during their basic specialization stage of sports training. Methods and procedures. This scientific approach led to the conduct of an ascertaining experimental study in the junior team of Deva and the National College "Cetate Deva", applied to a group of 19 female gymnasts, 12 to14 years old, all of them having the same training program. The research used the method of bibliographic study; the method of questionnaire; "KyPlot" statistical-mathematical method; ANOVA parametric test of comparison and graphical representation test - Excel. The assessment of the psychological score was performed by applying a questionnaire to a number of 3 coaches who work with junior gymnasts on different apparatus (vaults, uneven bars and beam). The questionnaire included 25 items that were used by means of calculation formulas to assess gymnasts` psychological scores, converted into indices, namely: goal-orientation index (GOI), self-confidence index (SCI), index of the ability to concentrate (IAC), index of performance capacity increase (IPCI) and training capacity index (TCI). Results. The results of testing the means of gymnasts` personality qualities indices were compared to the assessment scale of the psychological score and to the performances achieved in two competitions (National Juniors` Individual Championships, Deva 2012 and National Masters Championships One.ti, 2012), especially on the apparatus where worked the coaches-subjects of the survey. Conclusions. The assessment of the psychological score of junior gymnasts by each coach separately shows that there are no significant differences in the expression of personality qualities during training, except the goal-orientation index that has significant differences at P<0.05, which invalidates the hypothesis proposed by the research. The comparative analysis of personality qualities indices and the performances achieved in competitions highlight the influence of the development level of personality qualities upon the capacity for performance of the junior gymnasts - subject of the research.